2021
DOI: 10.3390/children8050353
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Inflation Reduces Pulmonary Blood Flow during Resuscitation with an Intact Cord

Abstract: The optimal timing of cord clamping in asphyxia is not known. Our aims were to determine the effect of ventilation (sustained inflation–SI vs. positive pressure ventilation–V) with early (ECC) or delayed cord clamping (DCC) in asphyxiated near-term lambs. We hypothesized that SI with DCC improves gas exchange and hemodynamics in near-term lambs with asphyxial bradycardia. A total of 28 lambs were asphyxiated to a mean blood pressure of 22 mmHg. Lambs were randomized based on the timing of cord clamping (ECC—im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There are reports of reduced blood flow to the heart with breathing movements. Newborn lamb experiments found that the umbilical venous flow was markedly reduced with each breath [72] and that a 30-s sustained inflation, even with delayed cord clamping, prevented the lamb's blood from flowing into the lung via the pulmonary artery and inferior vena cava [73]. A randomized control trial comparing sustained inflation with usual ventilation in human preterm infants was stopped because more early deaths occurred in the group of infants with sustained inflation [74].…”
Section: Notes On Breathingmentioning
confidence: 99%
“…There are reports of reduced blood flow to the heart with breathing movements. Newborn lamb experiments found that the umbilical venous flow was markedly reduced with each breath [72] and that a 30-s sustained inflation, even with delayed cord clamping, prevented the lamb's blood from flowing into the lung via the pulmonary artery and inferior vena cava [73]. A randomized control trial comparing sustained inflation with usual ventilation in human preterm infants was stopped because more early deaths occurred in the group of infants with sustained inflation [74].…”
Section: Notes On Breathingmentioning
confidence: 99%
“…A recent newborn lamb experiment found that the umbilical venous flow was markedly reduced with each breath [42]. In another newborn lamb study, a 30-s sustained inflation, even with delayed cord clamping, prevented the lamb's blood from flowing into the lung via the pulmonary artery and inferior vena cava [43]. A randomized control trial comparing sustained inflation with usual ventilation in human preterm infants was stopped because more early deaths occurred in the infants with sustained inflation [44].…”
Section: Breathing After Birthmentioning
confidence: 99%